Analise de políticas de reposição de estoque sob incerteza: aplicação em peças de manutenção de uma mineradora de ouro - Adriana Haueisen Pechir (2017)
This study contemplates an inventory replacement system when both demand and leadtime are stochastic. A simulation model was developed in R software with the objectiveof dening the stock policy which minimizes the inventory expected cost. Some maintenance items of a gold mining were used to apply the model. The selection of the goods was based on the criteria of criticality, inventory value and consumption frequency. In general, they are highly priced items and their shortage impacts directly in a production shutdown because they are spare parts of important equipments in the mining operation. They were analyzed also in some scenarios of leadtime variability in order to calculate the gain related to the actual scenario, in case of an increase of the supplier performance. Through the simulation model it was possible to conclude that there are opportunities of an expected cost reduction without a signicantly decrease of the service level. The model can also be applied to help in decision-making topics related to the other goods managed in stock to decide the quantity and the right time for the replacement.